Ohyake (公) czy watakushi (私) i puraibashii (プラ イバシー) ? Przestrzenie i artefakty systemu edukacji specjalnej i inkluzyjnej w Japonii: Raport z wizualnej mikroetnografii edukacyjnej - Borowska-Beszta, Beata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The presented research is a microethnographic report from a visual ethnography undertaken in May 2016, in 6 Japanese schools and 1 adult support center with disabilities located on island Kyushu in Fukuoka Prefecture. The study deals with a issues of the educational material culture and refers to the study of space and school artifacts designed in schools for students with special educational needs – understood as intellectual disabilities and for adults with such potential as well. The research was grounded in E. Schein’s organizational culture, furthermore on the concept of private space and public space described by T. Tamura and my author’s concept developed at the reinterreted role of the handicapped human in stationary institution published by W. Wolfensberger’s (1969).